Pengaruh Biaya Service terhadap Kepuasan Konsumen (Studi Kasus Trio Motor Sampit) - Yuliana, Yuliana (Keizai, 2023)
This research illustrates the role of motor vehicles in daily activities, particularly motorcycles, which have become favorites amidst dense urban mobility. Trio Motor Sampit, as an official service provider of Honda, offers quality-guaranteed services. Despite the higher service costs at Trio Motor Sampit, the number of customer visits increases from month to month. This indicates that most consumers are not influenced by the higher prices and continue to choose quality services. The research findings indicate that cost and service do not have a significant influence on customer satisfaction at Trio Motor Sampit. Higher costs do not affect consumers' decisions to use Trio Motor Sampit's services.